2010
DOI: 10.2174/1874396x01004010050
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Approaches to Predict Biomass Co-firing with Pulverized Coal

Abstract: The main motivation for co-firing coal with biomass is carbon dioxide emission reduction, while it can also lead to sulfur oxide reduction and suppress formation of nitric oxide from fuel nitrogen. Due to the fact that the coal is mainly used for power generation in its pulverized form, the emphasis in co-firing technologies is often given to co-combustion of pulverized biomass and coal. This facilitates the modeling approach to biomass combustion, since it may be considered in a way similar to the coal dust m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
(198 reference statements)
0
15
0
Order By: Relevance
“…Compared to biomass, coal presents higher C content (84%), higher LHV, and lower volatile matter. On the other hand, biomass presents lower contents of ash and pollution elements, such as N and S (Beloševic 2010). Coal-fired power plants provide over 42% of the electricity supply for the world.…”
Section: Replacement Of Fossil Fuels and Co 2 Retentionmentioning
confidence: 99%
“…Compared to biomass, coal presents higher C content (84%), higher LHV, and lower volatile matter. On the other hand, biomass presents lower contents of ash and pollution elements, such as N and S (Beloševic 2010). Coal-fired power plants provide over 42% of the electricity supply for the world.…”
Section: Replacement Of Fossil Fuels and Co 2 Retentionmentioning
confidence: 99%
“…Non-microalgal biomass particles are normally much bigger than pulverised coal and the amount of energy required for grinding of the biomass to a diameter of less than 1 mm (2-3 % of the heating value) is almost double that required for coal pulverisation (0.9-1.2 % of the heating value). The energy requirements for biomass pulverisation increase significantly (>20 % of the heating value) for fibrous and or moist biomass (Belosevic 2010). The combustion of biomass can generate fine particle emissions which can be harmful to health, with the amount, type and quantity of particulate emissions being influenced by biomass type, combustion technology and emission control equipment (Sippula 2010).…”
Section: Direct Combustionmentioning
confidence: 99%
“…These boilers are normally operated solely to generate electricity but can also be operated to simultaneously generate a combination of heat and power [37]. It is found that there is a growing interest in the use of biofuels for energy purposes due to various reasons such as reduction in dependency on imported oil, generation of 20 times more employment, mitigation of greenhouse gases [38][39][40], and reduction of acid rain [41]. It is a thumb rule that co-combustion of mixtures of biomass waste-based fuel and coal with energy input of the biomass up to 10% causes slight decrease in N 2 O emissions and may cause only mild or practically no operational problems [42].…”
Section: Biofuel-fired Boilermentioning
confidence: 99%